(untitled) - Syngress Media, Inc. (Berkeley, Calif., 2000)
The only classroom-based training and self-assessment system! Osborne's CCNA Cisco Certifed Network Associate Study Guide provides 100% complete coverage of all objectives for exam 640-507. Based on 200,000+ hours of IT training experience, the book contains hundreds of practice exam questions and hands-on exercises. The CD-ROM features full CertTrainer CBT software with interactive tutorials and lab simulations, plus the new ExamSim adaptive test engine
Keywords: Telecommunications engineers,Computer networks,Kỹ sư viễn thông,Mạng máy tính; Certification, Examinations,Chứng chỉ,Thi